2014
DOI: 10.7243/2055-2386-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high intensity interval training on diabetic obese women with polyneuropathy: a randomized controlled clinical trial

Abstract: Purpose: To investigate the effect of high intensity interval training on diabetic obese women with polyneuropathy. Methods: In rehabilitation clinics. A double blinded controlled randomized study including 40 type II diabetic women with polyneuropathy having class II central obesity, mean age 48.23±2.4 years. Patients were randomized equally into Group (A); (study), received high intensity interval training on cycle ergometer and group (B); (control) received moderate intensity aerobic training for (3 times/w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
10
1
Order By: Relevance
“…The above-mentioned findings seem to be in conformity with the results of those studies in which HIT was accompanied by improving glycemic control in obese and/or patients with T2D (36)(37)(38). Several studies have recently demonstrated that SIT appeared to be a very timeefficient exercise regime that shared many of the metabolic adaptations as traditional endurance exercise training did (36,39,40).…”
Section: Discussionsupporting
confidence: 87%
“…The above-mentioned findings seem to be in conformity with the results of those studies in which HIT was accompanied by improving glycemic control in obese and/or patients with T2D (36)(37)(38). Several studies have recently demonstrated that SIT appeared to be a very timeefficient exercise regime that shared many of the metabolic adaptations as traditional endurance exercise training did (36,39,40).…”
Section: Discussionsupporting
confidence: 87%
“…Our study’s IC intervention did not induce any changes in HOMA-IR, although it did result in modest improvements in muscle mass in the OW group ( Table 3 ). Our findings seem to be inconsistent with those of previous studies demonstrating that high-intensity training was accompanied by improved glycemic control in people with obesity and/or type 2 diabetes [ 43 , 44 ]. On the other hand, it should be recognized that the HOMA-IR assessment is not always sensitive to small but significant changes in insulin sensitivity [ 45 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, one research [ 17 ] has demonstrated that total and abdominal fat loss seems to be lowered more by HIIT than traditional continuous endurance training. Additionally, 15 weeks of 3 weekly sessions of HIIT on bicycle ergometer among diabetic obese women with polyneuropathy were found to be distinctly effective in lowering waist circumference, neuropathic pain, and hyperglycaemia as opposed to moderate intensity aerobic training [ 78 ].…”
Section: Discussionmentioning
confidence: 99%